Penerapan Konseling Kelompok Berbantuan Mind mapping untuk Meningkatkan Kreatifitas dan Hasil Belajar - Ivan Riyadi; Lili Dahliani; Lily Hidayani; Rudini Rudini; Mahin Ainun Naim (Kuras Institute, 2022)
This article was written based on a unique consideration of the implementation of mind mapping in study groups as a strategy in the world of education, especially in the realm of education management. This study proposes a strategic framework that can help link learning services with study group counseling mind mapping. This research uses descriptive qualitative research method. The sources of data used in this research are primary and secondary. Mind mapping of group counseling To get a complete picture in this article, a qualitative approach is used. Research results in counseling services. Management functions include; planning, organizing, directing and controlling. Therefore, management is defined as the process of planning, organizing, leading, and controlling learning efforts. Mind mapping of study group counseling is an art in teacher skills to be applied in various fields, especially counseling guidance.